Using cameras to index waterfowl abundance in winter-flooded rice fields - Firth, Alexandra G. (MethodsX, 2020)
Extensive wetland habitat loss across the continental United States has caused post-harvested rice fields to become an important surrogate wetland habitat for migratory waterfowl. Flooded rice fields used by waterfowl have the potential to provide agronomic benefits to soil. Increasing interest in the reciprocal relationship between birds and flooded rice fields has given rise to many studies that aim to quantify bird abundance. However, surveying large flocks of birds in open agricultural fields is challenging because traditional ground and aerial surveys can cause birds to flush or re-allocate spatially, thus biasing counts that are reflected in following management practice recommendations. To avoid this, we used camera surveys and an open-access image manipulation program to estimate 24-h bird use of rice fields. Indices of bird abundance from counts were used to estimate fecal matter input to rice fields. Camera surveys have the potential to limit biases seen in other methods because of their ability to capture bird use over a 24-h period over an entire season and the ability for multiple researchers to survey the same site. • Surveying bird flocks by traditional ground or aerial surveys can bias bird abundance estimates. • Camera surveys of waterfowl in rice fields were used to estimate bird abundance and fecal matter input. • Camera surveys reflect static bird use over 24-h which can lower bias seen in traditional methods.